NETWORK VIRTUALIZATION PERFORMANCE ANALYSIS ON OPENSTACK CLOUD COMPUTING INFRASTRUCTURES - Võ Nhân Văn; Lê Minh Chí; Nguyễn Quốc Long; Lê Đắc Nhường (Tạp chí Khoa học Đại học Đà Lạt)
Cloud computing has become popular in IT technology because of its advantages that focus on flexible, scaling, resources and services which help customers easy to build their own on-demand IT system easily. Moreover, Cloud computing also can assist users to balance, share, and manage IT resources among customers to get better performance of compute and storage. OpenStack, a new open source cloud computing framework which was a built-in modular architecture and focused on IaaS. OpenStack also focuses on NaaS by using network virtualization technology with native opensource intergrated solution – openvswitch and supports other commercial solutions from vendors. OpenStack nowadays has been popularly in business. This paper does a research on network performance on OpenStack network module code named Neutron. The parameters in virtualization network of OpenStack related to network performance such as throughput, package loss, time and delay of data transmission are estimated through UDP protocol using IPERF benchmarking tool. Our research investigated the possible internal traffic flow patterns and evaluated network performance of each pattern on OpenStack cloud computing environment.